Rekonstruk Buku Ajar Pendidikan Agama Islam Bermuatan Paham Radikal di Sekolah - A. Jauhar Fuad (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2017)
This article is limited to the study of literature about the handling of radicalization at educational institutions. More specifically the authors want to add as much information, so in this seminar to strengthen the study of literature and the data that can Strengthen further research. Preliminary results as follows: radicalism entered through textbooks, by changing the religious understanding of teachers and students, the book that is used is the official book published by the government and private institutions through worksheets. On the basis of the above problems, the authors do try to look back on some of the teaching materials PAI charged radical as revised by the government and by society in order to improve the textbook so that understanding can Radically lost. It is necessary to reorientation handling of radicalization has been done and understood by as great people. Efforts to stem radicalism which has been more focused on terrorists or combatants of war, not much is done as a precaution understand and radical action.Keywords: de-radicalization, textbook, Islamic religious education